A novel dihydro phenylquinazolinone-based two-in-one colourimetric chemosensor for nickel(ii), copper(ii) and its copper complex for the fluorescent colourimetric nanomolar detection of the cyanide anion. Issue 73 (21st December 2020) - Sahu, Meman; Manna, Amit Kumar; Chowdhury, Shubhamoy; Patra, Goutam Kumar
Abstract : A novel colorimetric chemosensor L has been developed for the detection of Ni 2+ and Cu 2+ ions. The obtained L –Cu 2+ complex can be used as a new cascade fluorescent-colorimetric sensor for the nanomolar detection of CN − ions. This chemosensor has practical application. Abstract : Currently, considerable efforts have been devoted to the detection and quantification of hazardous multi-analytes using a single probe. Herein, we have developed a simple, environment-friendly colourimetric sensor for the sensitive, selective and rapid detection of Ni 2+ and Cu 2+ ions using a simple organic Schiff base ligand L in methanol–Tris–HCl buffer (1 : 1 v/v, 10 mM, pH = 7.2). The probe L exhibited a binding-induced colour change from colourless to yellow and fluorescence quenching in the presence of both Ni 2+ and Cu 2+ ions. The interactions between L and the respective metal ions were studied by Job's plot, electrospray ionisation-mass spectrometry (ESI-MS), Fourier-transform infrared spectroscopy (FT-IR), density functional theory (DFT) and time-dependent density functional theory (TDDFT) calculations. The limit of detection (LOD) of L towards Ni 2+ and Cu 2+ was calculated to be 7.4 × 10 −7 M and 4.9 × 10 −7 M, respectively. Furthermore, the L –Cu 2+ complex could be used as a new cascade fluorescent-colourimetric sensor to detect CN − ions with a very low level of detection (40 nM). Additionally, L could operate in a wide pH range, and thus was successfully applied for the detection and quantification of Ni 2+ and Cu 2+ in environmental samples, and for building OR- and IMPLICATION-type logic gates.